Question

( begin{aligned}(x-a)(x-b)=c & Rightarrow x^{2}+(-a-b) x+(a b-c)=0 therefore & x+beta=a+b & alpha cdot beta=a b-c (x-alpha)(x-beta)+c &>0 end{aligned} )
3) ( x^{2}-(x+beta) x+infty,+c=0 )
( z^{2}-(a+b) x+a b-c+c=0 )
( rightarrow quad x^{2}-(a+b) x+a b=0 )
2) ( (x-a)(x-b)=0 )
Rootsar ( a, b )

# (3) (4) tan + tan+tan 2-d2" tan tan 2 + tan Iran 4+ tan 2 tan e=0 3 Tower, A CG Towe 5 GIN: (4) a + c, b + c 8 (X - a) (x - b) = C, C+0. Then the roots of the equation equation be the roots of the equation (X - a) (x - b) = C, C+ Let a, (3) a, b (x - a) (x-B) + C = 0 are : (2) b c (1) a, c 1 52, IPIA, Near City Mall, Jhalawar Road, Kota (Raj)-324005 Tahind City Mall, Jhalawar Road, Kota (Raj-324005

Solution